Risk Factors of Acute Respiratory Infections Incidence in Toddlers of the Working Area of Puskesmas Inerie Ngada District - Yohanes Meli; Marylin Susanti Junias; Ribka Limbu (Lontar : Journal of Community Health, 2020)
The main contributor to the decline in life expectancy in low-income countries is acute respiratory tract infections (ARIs/ISPA). Risk factors of ISPA events consist of intrinsic and extrinsic factors. This research purposed to analyze the risk factors of ISPA incidence in the working area of Puskesmas Inerie. This research was descriptive-analytical research with a cross-sectional design. Data collection employed interviews with 88 mothers who have toddlers, obtained by simple random sampling technique. Data analysis used a chi-square test. The data analysis results showed that the four research variables, namely nutritional status, occupancy, ventilation, and smoking behavior, related to ISPA incidence with p-value=0.000, 0.000, 0.001, and 0.01 consecutively. Poor home conditions lead to an increased risk of ISPA disease in toddlers. Therefore, the local community should improve the physical condition of the house and the nutritional status of toddlers in the working area of Puskesmas Inerie.